APPLICATION OF PHYSICAL AND MATHEMATICAL METHODS AT THE EXAMINATION OF DRY BREAKFAST FOODS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The object of the study is the breakfast cereals from different manufacturers. The aim of the article is to prove the possibility of using physical and mathematical methods for studying the dispersed composition of breakfast cereals during their commodity and customs examinations and expanding the possibilities of exporting these products based on assessing their quality.
Keywords: dry breakfast foods; commodity examination; differential distribution functions of pores by radius